Robust beamforming based on the worst-case performance optimization with positive semi-definite constraints - Ding-jie XU; Rui HE; Feng SHEN (Tongxin xuebao)
For the robust adaptive beamforming problem of the gen l signal models, a robust beamforming algorithm based on the worst-case performance optimization with positive semi-definite constraints was proposed. A simple robust adaptive beamformer was derived by modeling and transforming. Not only an approximate closed-form solution to the optimal weight vector was derived with low complexity, but also the performance improvement could be obtained. The final simulation attests its effectiveness and correctness.